Evaluating the impact of monetary policy on inflation in Sub-Saharan Africa - Asiamah, Michael (Asian Journal of Economic Modelling, 2024)
This paper aims to assess the effect of monetary policy on inflation in Sub-Saharan Africa. The recent global economic crises have greatly brought about pervasive price distortions in many economies of Sub-Saharan Africa (SSA). However, a credible and sound monetary policy can provide a solution by influencing real economic outcomes. This paper employs the system General Method of Moment (GMM) technique based on a sample of 23 countries in SSA using a quarterly panel dataset for the period 2013-2022. According to the paper, contractionary monetary policy leads to a fall in inflation, and vice versa. Additionally, the inflation, interest rate, potential growth rate, and exchange rate negatively and significantly influence inflation in SSA. Further, inflation square, public debt, and oil prices positively and significantly influence inflation in SSA. Moreover, type of exchange rate regimes pursued by countries in SSA positively influences inflation. Monetary policy significantly influences inflation in SSA. This paper contributes to knowledge in terms of the monetary policy and inflation relationship and sheds more insight into how monetary policy brings probable changes in inflation in SSA, which informs policy decisions of monetary authorities.